Conducting educational design research - McKenney, Susan E.; Reeves, Thomas C. (Thomas Charles). (New York : Routledge, 2012)
'Among the wide variety of backgrounds, many of those active in defining and applying educational design research appear to have arrived through an interest in psychology, the learning sciences or instructional design. Although most design studies are carried out in multi-disciplinary teams, participants need to conceptually understand the marriage between the design discipline and scientific research traditions. Conducting Educational Design Research emphasises the application of design knowledge and skills in research programs, guiding readers through the various disciplinary backgrounds and scientific developments current today. Therefore, this book on design research will be especially useful for faculty and students in (a) graduate education programs where exposure to research methodologies is strong but exposure to design methodologies is limited; and (b) graduate programs in instructional design where participants have strong backgrounds in design, but may lack the scientific research orientation. In a time when design research is gaining momentum, it seems notable that educational research programs are being confronted with the randomized field trials movement; and educational design programs are at risk of diluting their design character as valuable curricular time is being usurped by more traditional research skills. This book not only offers an invaluable classroom resource, it also provides for the ongoing university dialogue on how to best prepare the next generation of educational researchers'-- Provided by publisher.
Keywords: Instructional systems -- Design -- Research